Durability assessment of asphalt binder. (20th March 2018) - Angius, Ezequiel; Ding, Haibo; Hesp, Simon A.M.
Highlights: AASHTO M 320 lacks sensitivity and passes many binders of low durability. DENT testing separates binders with a high degree of sensitivity in ductile failure. Grade losses due to extended PAV aging are correlated with losses in the extended BBR. Limiting EBBR grades are highly correlated with limiting phase angle temperatures. Abstract: Test results are presented for 24 asphalt binders with the aim to compare various measures of durability. Surprisingly high correlations were found between disparate measures of durability but practical considerations make certain tests preferable. A comparison is provided between AASHTO M 320 grades, critical crack tip opening displacements, extended bending beam rheometer grades and grade losses, differences in limiting temperatures (ΔTc ), and simple limiting phase angle temperatures (T(δ)), on aged residues. The limiting phase angle temperature appears to be a convenient surrogate property that accurately predicts thermoreversible aging tendencies. Several binders performed poorly, likely because they contained unwarranted reclaimed asphalt.